scoateti factorul comun : 24a⁴b³ + 42a³b³ - 18a²b
Răspunsuri la întrebare
Răspuns de
1
6*a^2*b*(4*a^2*b^2+7a*b^2 -3)
SeeSharp:
cu ^ = la puterea
Răspuns de
1
24 a⁴ b³ + 42 a³ b³ - 18 a² b =
4· 6 a²⁺² b¹⁺² + 6· 7 a²⁺¹ b¹⁺² - 3 ·6 a² b¹⁺⁰=
4· 6 a² ·a²· b¹· b² + 6 ·7 a²·a¹·b¹· b² - 3· 6 a²· b¹·b⁰=
4· 6 a² ·a²· b¹· b² + 6 ·7 a²·a¹·b¹· b² - 3· 6 a²· b¹·b⁰=
6 a²· b¹·( 4a²·b² + 7 ·a¹· b² -3·b⁰)=
6 a²· b¹·( 4a²·b² + 7a¹·b² - 3)=
4· 6 a²⁺² b¹⁺² + 6· 7 a²⁺¹ b¹⁺² - 3 ·6 a² b¹⁺⁰=
4· 6 a² ·a²· b¹· b² + 6 ·7 a²·a¹·b¹· b² - 3· 6 a²· b¹·b⁰=
4· 6 a² ·a²· b¹· b² + 6 ·7 a²·a¹·b¹· b² - 3· 6 a²· b¹·b⁰=
6 a²· b¹·( 4a²·b² + 7 ·a¹· b² -3·b⁰)=
6 a²· b¹·( 4a²·b² + 7a¹·b² - 3)=
Alte întrebări interesante
Matematică,
9 ani în urmă
Germana,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă